Infrared thermography - evaluation of the results reproducibility - Elton Bauer (2015)
Purpose - Infrared thermography is increasingly being used to diagnose pathologies in buildings, such as façade defects. The purpose of this paper is to assess the results reproducibility and the equipment influence on the measurements. To do so, it was defined as case study the assessment of rendering delamination. Design/methodology/approach - Two infrared cameras of different makers were used to detect the presence of defects deliberately created in specimens. The tests were done in the laboratory with a heat source. The defects were detected through a temperature gradient between the zones with and without defect. Findings - With this thermographic imaging, it was possible to identify the defects in the specimen both qualitatively and quantitatively. The results were found to be reproducible in the three cycles performed. The influence of the equipment on the results was of little significance for the quantitative assessment criterion - temperature difference between zones with and without defect", but for the criterion "absolute surface temperature", the difference in the results yielded by the two cameras was around 1.8°C. Originality/value - The results suggest that there is reproducibility of the measurements, considering both the qualitative and quantitative approach, when assessing delamination, irrespective of the maker of the equipment used. The influence of the equipment on the results depends on the quantitative assessment criterion used. (c) Emerald Group Publishing Limited.